THU0339 Management of Achilles Tendinopathy in Reactive VS Degenerative Stage: A Prospective, Randomized, Controlled Trial Evaluating the Efficacy of A Dietary Supplement Associated to Eccentric Training or Passive Stretching. (10th June 2014) - Balius, R.; Άlvarez, G.; Barό, F.; Jiménez, F.; Pedret, C.; Pujol, M.; Lόpez, D.J.; Martínez, D.; Ramirez, P.; Martinez-Puig, D.
Abstract : Background: Tendinopathy is an overuse tendon injury that results in pain, decreased exercise tolerance and a reduction in function, being a major problem in sports and occupational medicine. A new pathology model has recently been proposed dividing tendinopathies into different stages according to severity, allowing rational placement of treatments at each different stage. Objectives: The aim of this study is to evaluate the efficacy and safety of 3 different interventions: eccentric training (EC), eccentric training + Tendoactive®, a dietary supplement containing Mucopolisaccharides, type I Collagen and Vitamin C (EC+MCV), and passive stretching program + MCV (PS+MCV). It is also studied whether there is different response pattern to the mentioned treatments depending on the pathology stage. Methods: In this randomized, controlled, multicenter trial fifty-nine patients were randomly assigned to 1 of 3 treatment groups, and classified in one of two subgroups designed according to the Cook & Purdam pathology model: reactive vs degenerative tendinopathy. Patients were evaluated at baseline, 6 and 12 weeks with the Victorian Institute of Sports Assessment-Achilles (VISA-A) questionnaire. Pain was evaluated at rest and during activity using a visual analog scale (VAS), and evolution of tendon structure was assessed by ultrasound. Results: A significant improvement in VISA-A score, pain at rest and pain during activity were detected in all 3 treatment groups at 6 and 12 weeks follow-up, when compared to baseline. In patients with reactive tendinopathy the reduction on pain at rest was significantly greater in the groups supplemented with MCV than in the EC group (P<0.05), while the VISA-A score tended to obtain a better recovery in the EC+MCV treatment than in the EC alone (P=0.069). In patients with degenerative tendinopathy, a significant reduction of the bilateral thickness and neovascularization degree of the affected tendon, were detected in the PS+MCV group. Conclusions: A dietary supplement containing mucopolisaccharides, type I collagen and vitamin C, seems to be safe and effective for management of tendinopathies, providing some additional benefit to the physical therapy. This is especially evident in early stages of the disease, when the tendon doesn't present severe matrix and vascular changes. References: Cook J, Purdam C R. Is tendόn pathology a continuum? A pathology model to explain the clinical presentation of load-induced tendinopathy. Br J Sports Med 2009;43:409-416. Shakibaei M, Buhrmann C, Mobasheri A. Anti-inflammatory and anti-catabolic effects of TENDOACTIVE® on human tenocytes in vitro. Histol Histopathol. 2011 Sep;26(9):1173-85. Nadal F, Bové T, Sanchís D, Martinez-Puig D (2009) Effectiveness of treatment of tendinitis and plantar fasciitis by tendoactive™. Osteoarthritis and Cartilage, Volume 17, Supplement 1, Page S253. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.5533